Understanding the Factors That Affect the Adoption of Innovative High-Technology Brands: The Case of Apple iPhone in Malaysia - Rageh, Ahmed (The Haworth Press Inc, 2012)
The purpose of this study is to examine how innovation attributes, social influence, and perceived risk can affect technology brand adoption. The impact of innovation attributes, social influence, and perceived risk on iPhone adoption has been tested through series of tests (i.e., reliability, exploratory factor analysis, confirmatory factor analysis, correlations, multiple regression analysis, and moderation effect of gender). The sample consists of 134 Malaysian students. Results revealed the importance of relative advantage, trialability, and social influence as key constructs in adoption intention. The study also showed that gender of the consumer has no moderating effect on the adoption intention. Practical guidelines are provided to marketing managers on how to use those factors to increase the adoption of new brands among customers.